2005
DOI: 10.1007/s11745-005-1492-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary n−6 and n−3 polyunsaturated fatty acids on peroxidizability of lipoproteins in steers

Abstract: The susceptibility of major plasma lipoproteins to lipoperoxidation was studied in relation to the FA composition of their neutral and polar lipids in steers given PUFA-rich diets. Two trials used, respectively, 18 ("sunflower" experiment, S) or 24 ("linseed" experiment, L) crossbred Salers x Charolais steers. Each involved three dietary treatments over a 70-d period: a control diet (CS or CL diets) consisting of hay and concentrate, or the same diet supplemented with oilseeds (4% diet dry matter) fed either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…The result was related to the fatty acid composition of PO and CLO. To the best of our knowledge, the formation of MDA is closely related to the oxidation of n‐3 and n‐6 PUFA (Scislowski et al ., ; Viau et al ., ). As shown in Table , PO and CLO possessed rather low PUFA levels (8.40% and 7.16% respectively).…”
Section: Resultsmentioning
confidence: 97%
“…The result was related to the fatty acid composition of PO and CLO. To the best of our knowledge, the formation of MDA is closely related to the oxidation of n‐3 and n‐6 PUFA (Scislowski et al ., ; Viau et al ., ). As shown in Table , PO and CLO possessed rather low PUFA levels (8.40% and 7.16% respectively).…”
Section: Resultsmentioning
confidence: 97%
“…PREVET (2014), http://dx.doi.org/10.1016/j.prevetmed.2014.10.013 LS-based diet might be responsible for observing higher oxidative stress symptoms in these cows (Castillo et al, 2003). Also, Scislowski et al (2005) reported that steers receiving duodenal infusion of linseed oil (rich in n-3 FA) were more susceptible to peroxidation than those receiving sunflower oil (rich in n-6 FA). But contrary to our results, they showed that feeding extruded linseed did not induced oxidative stress compared to extruded sunflower seed probably due to extensive ruminal biohydrogenation of PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…However, enriching diets with omega-3-rich FA (n-3 FAs), such as by supplementing linseed, may concurrently predispose cows to experience more symptoms of oxidative stress and subsequently disturb metabolic homeostasis (Gobert et al, 2009). Some researchers reported that n-3 FA supplementation to fattening steers (Scislowski et al, 2005) or rabbits (Tres et al, 2009) led to greater oxidative stress than omega-6 FA (n-6 FA) supplementation, but the effects of different FA on oxidative status of transition dairy cows that normally experience physiologic oxidative stress remains unclear (Turk et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of soya bean oil as a possible dietary source to improve the oxidative status of ruminants has been proposed by Scislowski et al. (). Positive impact on the antioxidant defence system may also be observed with the fish oil too, because its inclusion in the diets of rabbits (Hsu et al., ) and rats/hamsters (Erdogan et al., ; Muga and Chao, ) inhibited the oxidative stress and prevented the formation of free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress in ruminants occurs not only during periparturient period or heat stress but also when they receive diets rich in PUFA (Scislowski et al., ,b). Although dietary PUFAs are subjected to ruminal biohydrogenation, some of them escape from this process.…”
Section: Introductionmentioning
confidence: 99%